2015
DOI: 10.1021/acs.langmuir.5b00919
|View full text |Cite
|
Sign up to set email alerts
|

Time-Resolved Imaging Study of Jetting Dynamics during Laser Printing of Viscoelastic Alginate Solutions

Abstract: Matrix-assisted pulsed-laser evaporation direct-write (MAPLE DW) has been successfully implemented as a promising laser printing technology for various fabrication applications, in particular, three-dimensional bioprinting. Since most bioinks used in bioprinting are viscoelastic, it is of importance to understand the jetting dynamics during the laser printing of viscoelastic fluids in order to control and optimize the laser printing performance. In this study, MAPLE DW was implemented to study the jetting dyna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
72
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 77 publications
(75 citation statements)
references
References 28 publications
1
72
2
Order By: Relevance
“…One aspect of the printing process, which is influenced by these parameters, is the velocity of the hydrogel jet that might affect the vitality of printed cells. Zhang et al [16] demonstrated printing with jet velocities down to 10 m/s, while the jet velocities in our study have been about 50 m/s so far. Therefore, printing of alginate droplets with three different focal spot sizes (3000, 4000, and 7500 µm²) and the generated jet velocities have been investigated for different laser pulse energies ( Figure 9A).…”
Section: Focal Spot Size Variationcontrasting
confidence: 54%
“…One aspect of the printing process, which is influenced by these parameters, is the velocity of the hydrogel jet that might affect the vitality of printed cells. Zhang et al [16] demonstrated printing with jet velocities down to 10 m/s, while the jet velocities in our study have been about 50 m/s so far. Therefore, printing of alginate droplets with three different focal spot sizes (3000, 4000, and 7500 µm²) and the generated jet velocities have been investigated for different laser pulse energies ( Figure 9A).…”
Section: Focal Spot Size Variationcontrasting
confidence: 54%
“…3c-1 and c-2. For comparison, a high-concentration viscous NaAlg, which has a zero-shear-rate viscosity of approximately 3.1 Pa·s [27] but is not a yield-stress fluid, was extruded to examine the effect of viscosity on the extrudability. NaAlg filament formation is illustrated in Fig.…”
Section: Effects Of Nanoclay On Extrudabilitymentioning
confidence: 99%
“…The cavitation resulting from the ablation of titanium expanded with the energy converting to deformation of the sacrificed layer if any, viscous dissipation energy, surface energy, and potentially the kinetic energies to forming jets root from Rayleigh or Plateau-Rayleigh instability [30]. In Newtonian fluids, the jettability significantly depends on the Ohnesorge number Oh  =  η /( ρ l σR ) 1/2 and Weber number We  =  ρ l RU 2 / σ where η is the zero-shear viscosity, σ is the surface tension, R is the characteristic length that could be considered as the radius of the laser spot, and ρ l is the density of medium.…”
Section: Discussionmentioning
confidence: 99%